Gambaran Tingkat Pengetahuan Masyarakat Dalam Pemanfaatan Daun Sukun Pada Penyakit Degenerative di Kecamatan Cinunuk, Cileunyi Kabupaten Bandung. - Riasari, Hesti; Fitriansyah, Sani Nurlaela; Wibowo, Diki Prayugo; Hasanah, Siti Uswatun; Wirasutisna, Komar Ruslan; Restiasari, Anggi (Progran Studi Farmasi Universitas Mandala Waluya, 2024)
Health is a very important aspect in human life. Degenerative diseases are a serious challenge faced by modern society. Community service aims to describe the level of knowledge of the community in Cinunuk District, Cileunyi, Bandung Regency, as well as analyzing the extent to which breadfruit leaves are used in efforts to prevent and treat degenerative diseases. This community service was carried out on October 26 2023 at the Sebaguna Building, Cinunuk Cileunyi District, Bandung Regency in collaboration with Medina Farma Pharmacy. A total of 78 people took part in counseling activities related to degenerative diseases, plants used as herbal medicines, healthy lifestyles to prevent degenerative diseases, workshops on making breadfruit leaf tea products, health checks such as blood pressure, instant blood sugar, total cholesterol levels, accompanied by health counseling and distribution of pamphlets, 45 of them filled out the questionnaire online using g-form. The results of respondents before the counseling and workshop were 45.89%, indicating that the level of knowledge of respondents was very poor, after the counseling and workshop on making herbal tea preparations there was an increase in the knowledge of the people of Cinunuk District by 81 .48% with a high category of respondents' knowledge regarding degenerative diseases, plants that can be used as herbal medicine, the use of breadfruit leaves and their processing in the form of herbal tea preparations which makes it easier for people to consume them in traditional treatment efforts as preventive and curative.